Pillars for successful operationalization of one health as an ecosystem approach: experience from a human-animal interface in the Maasai steppe in Tanzania - Paul Gwakisa; Janeth George; Calvin Sindato; Anibariki Ngonyoka; Happiness Nnko; Justine Assenga; Sharadhuli Kimera; Moses Ole Nessele (BMC, 2023)
Abstract Background Solving complex public health challenges requires integrated approaches to health, such as One Health. A key element of the One Health approach is the interrelationship between human, animal and environmental health and the associated multistakeholder collaboration across many cultural, disciplinary, institutional and sectoral boundaries. Here we describe a pragmatic approach for One Health operationalisation basing on our long-term engagement with communities faced with health challenges in a human-livestock-wildlife interface in the Maasai steppe in northern Tanzania. Methods Using a qualitative study design we performed an outcome mapping to document insights on results integration from our previous project. Data were collected through participatory community meetings, in-depth interviews and field observations. Field notes were coded and analysed using inductive thematic analysis. Results We found that effective implementation of One Health interventions in complex ecosystems works best by understanding local conditions and their context and by working closely with the local people and relevant disciplinary players as one complex adaptive system. Community engagement, systems analysis, transdisciplinarity as well as political commitment played critical roles in successful operationalization of One Health. We have further emphasized that project ownership is as important to the local community as it is to the researchers. When used in combination, these elements (community engagement, systems analysis, transdisciplinarity) provide essential pillars for co-creation and maintaining collective action to set a common vision across disciplines, serving as inputs for a metrics-based toolbox for One Health operationalisation. Conclusion Considering the novelty and complexity of One Health operationalisation, there is need also to develop scorecard-based guidance for assessment of One Health programs at local and national level. This paper proposes a framework for the optimization of an ecosystems-based One Health approach for prevention and control of Vector-Borne Diseases implemented at the local, sub-national or national level.